TRANSFORMACJA USTROJOWA A CIĄGŁOŚĆ INSTYTUCJI PRAWNYCH – UWAGI TEORETYCZNE - Mańko, Rafał (Zeszyty Prawnicze, 2016)
Systemic Transformation and the Continuity of Selected Legal Institutions Summary Despite a systemic transformation a number of legal institutions servive. The existing conceptual framework does not account sufficiently for this phenomenon, hence the need to introduce and refine the concept of ‘legal survival,’ as applicable to a legal institution characterised by normative continuity, though often attended by a political, economic, social or ideological change in its social function.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />